Gender Differences in the Physical Health of Older People: The Case of Palungtar Municipality, Gorkha District, Nepal - Mani, Bijaya; Acharya, Suresh (Rural Development Journal, 2025)
This study examines gender differences in the physical health of older adults, highlighting critical disparities that influence longevity and quality of life. Notably, women often live longer than men but experience poorer health outcomes, such as higher rates of disability and chronic illnesses. These differences are complicated by factors like socioeconomic status, ethnicity, and access to healthcare, suggesting that gender disparities in health are influenced by a complex interplay of biological, social, and psychological factors. Utilizing a census method, this study collected comprehensive data from older people in Palungtar Municipality-5, Gorkha district through interviews using a structured questionnaire. This approach allowed for analysis of health conditions, lifestyle habits, and access to healthcare services. The study aims to provide a nuanced understanding of how societal norms and personal behaviors influence gender disparities in physical health, thereby informing targeted interventions to improve the health and quality of life for older men and women. The findings underscore the need for gender-sensitive health interventions. Women, in particular, face greater challenges in mobility and self-care, likely exacerbated by conditions such as osteoporosis. Additionally, this research challenges traditional stereotypes about personal hygiene, showing that older men and women maintain similar levels of neatness and cleanliness, reflecting broader cultural shifts or increased capability among older men. The study's outcomes stress the importance of considering gender-specific needs and barriers when designing health programs and policies to ensure equitable healthcare and support for all older adults.